Servicios ambientales del parque histórico y su incidencia económica para el cantón de guayaquil. año 2019 - Robalino Zambrano, José Andrés (2020)
The parks constitute extensions of territories protected by national and international laws to conserve natural resources and guarantee the socioeconomic well-being of the country. The objective was to economically value the environmental services of the Guayaquil Historical Park (PHG) through the total economic value method (VET). For this, interviews and surveys were applied to park visitors. During the visits carried out, it was found that the park is made up of forests, mangroves and ornamental species due to natural regeneration, there are larger and smaller animal species, as well as poultry and wild birds that are in danger of extinction. With the data collected, a tourist attraction rating of 98 was obtained, which corresponds to a ranking IV, which means that it is an exceptional attraction and of high significance for the tourist market attractive to visitors. According to the contingent valuation method, users are willing to pay $ 32 to preserve the PHG, with 4% of the target population being established in the 2020-2024 period, generating an average population of 24,256 whose income amounts to an average of $ 776,197.54. . The zoning indicates that the surface and the species immersed in the park provide environmental services with a value of $ 20,015.9, based on ecosystem functions such as gas regulation, climate, erosion control, nutrient recycling, shelter, food production, recreation and habitat. Finally, it is concluded that the economic incidence of the Guayaquil Historical Park is sustainable since the cost-benefit ratio is greater than one due to the environmental and recreational services that it provides to Ecuadorians. KEYWORDS: Environmental economics, historical park, natural resources, contingent valuation